Genetic polymorphism of Arg213His variant in the SULT1A1 gene is associated with reduced susceptibility to lung cancer in North Indian population - Walia, Harleen Kaur; Singh, Navneet; Sharma, Siddharth (Xenobiotica, 2021)
Sulfotransferases (SULTs) are phase II detoxification enzymes that is involved in the biotransformation of many compounds including tobacco carcinogens. A polymorphism in the SULT1A1 (Arg 213 His) gene results in reduced enzyme activity. We investigated the association between the SULT1A1 (Arg 213 /His) genotype and lung cancer (LC). This case-control study comprised of 550 cases and controls, matched on age, gender and smoking status. The variant genotype exhibited no association with LC risk, even after stratification on basis of histological subtypes. Male LC patients carrying the variant His 213 allele ( p = 0.02) did not exhibit an increased risk towards LC. Smokers harbouring the Arg/His genotype did demonstrate a reduced risk towards LC (AOR = 0.70; p = 0.019). Furthermore, the LC subjects who were heavy smokers and harbouring the Arg/His genotype (AOR = 0.28; p = 0.019) did not show a genetic predisposition towards LC susceptibility. The subjects who smoked pack years of above 40 and carrying the His/His (AOR = 0.28; p = 0.036) genotype were found to have a reduced risk for LC. Furthermore, 473 subjects were analysed in regards to overall survival, wherein the His/His genotype exhibited better OS than Arg/Arg genotype (11.30 vs. 8.07 months). This study provides evidence of no genetic predisposition towards LC risk associated with SULT1A1 Arg 213 His polymorphism in relation to tobacco smoking.